Isolation and identification of potential nematophagous fungi in banana farms from the Huetar Atlantic Region of Costa Rica - Ugalde-Monge, Berlioth (2024)
Introduction. Banana production is one of the most significant economic activities for the country. However, it faces serious challenges due to the presence of various pathogens, among the most significant are plant-parasitic nematodes that affect crop yield and quality. The use of nematophagous fungi (NF) for biological control of nematodes is an alternative to reduce the application of synthetic chemicals in agricultural crops. In Costa Rica there is a great variety of fungi due to the diversity of soils. Therefore, the isolation and correct identification of these fungi is crucial to determine their antagonisti potential. Objective. To isolate and identify the potential nematophagous fungi (PNF) present in soil samples from banana plantations at the Huetar Atlantic region. Materials and methods. Six soil samples from the Huetar Atlantic region of Costa Rica were analyzed by the agar water sprinkling plates method in search of PNF. For PNF selection and purification, Petri dishes with potato dextrose agar (PDA) were used, identifying morphological structures for diagnosis at genus level. Morphologically identified fungi were replicated and preserved in vials with PDA and in mineral oil at 4°C. DNA was extracted from the isolated PNF and through PCR amplification (Polymerase Chain Reaction) and sequencing of different regions of the genome (ITS, tef 1-alpha, rpb2 and β-tubulin), they were molecularly identified. Results. Twelve fungi were isolated and identified, including Trichoderma asperellum, Penicillium steckii, Purpureocillium lilacinum, Fusarium oxysporum, Fusarium sp., Fusarium pseudocircinatum, and Talaromyces sp. Conclusion. The correct discovery and identification of PNF underscores the importance of investigating its application in integrated pest management programs, as well as the need to evaluate its efficacy and safety under different agroecological conditions to maximize its positive impact on agriculture.